An in‐vitro study of subretinal perfluorocarbon liquid (PFCL) droplets and the physics of their retention and evacuation. Issue 8 (5th March 2021) - Chan, Yau Kei; Laybourne, James P.; Ng, Chiu On; Saha, Chinmoy; Yap, Hazel Pik Yen; Chandra, Aman; Steel, David H.; Sandinha, Maria T.; Wong, David
Abstract: Purpose: To investigate the physics associated with the retention and removal of subretinal perfluorocarbon liquid (PFCL), as inspired by a series of anecdotal cases of spontaneous 'disappearance' of subretinal PFCL. Methods: The profiles of subretinal PFCL in situ from published OCT images were studied and compared with that of PFCL droplets resting on a hydrophilic surface in vitro . A mathematical model based on Sampson's and Poiseuille's formula was developed to explain how evacuation of subretinal PFCL without aspiration could occur. Results: The mathematical model suggested that in vivo subretinal PFCL can completely evacuate in less than a second via a 41‐guage retinal hole. Perfluorocarbon liquid (PFCL) droplets in situ subretinally substantially varied in their aspect ratios (from 0.28 to 2.71) and their contact angles with the retinal pigment epithelium (from 98° to 155°). Conversely, PFCL in vitro had aspect ratios and contact angles close to 1 and 150° respectively. Conclusion: This study showed evidence that stretching of the retina to accommodate subretinal PFCL occurs, which might be responsible for the varied profile of the droplets and resultant forces that can cause retinal holes, and spontaneous evacuation of large PFCL droplets. By filling the vitreous cavity with PFCL, a small retinotomy alone might allow spontaneous evacuation without the need for aspiration.